The extended Toronto criteria for liver transplantation in patients with hepatocellular carcinoma: A prospective validation study. Issue 6 (30th June 2016) - Sapisochin, Gonzalo; Goldaracena, Nicolas; Laurence, Jerome M.; Dib, Martin; Barbas, Andrew; Ghanekar, Anand; Cleary, Sean P.; Lilly, Les; Cattral, Mark S.; Marquez, Max; Selzner, Markus; Renner, Eberhard; et al.
Abstract : The selection of liver transplant candidates with hepatocellular carcinoma (HCC) relies mostly on tumor size and number. Instead of relying on these factors, we used poor tumor differentiation and cancer‐related symptoms to exclude patients likely to have advanced HCC with aggressive biology. We initially reported similar 5‐year survival for patients whose tumors exceeded (M+ group) and were within (M group) the Milan criteria. Herein, we validate our original data with a new prospective cohort and report the long‐term follow‐up (10‐years) using an intention‐to‐treat analysis. The previously published study (cohort 1) included 362 listed (294 transplanted) patients from January 1996 to August 2008. The validation cohort (cohort 2) includes 243 listed (105 M+ group, 76 beyond University of California San Francisco criteria; 210 transplanted) patients from September 2008 to December 2012. Median follow‐up from listing was 59.7 (26.8‐103) months. For the validation cohort 2, the actuarial survival from transplant for the M+ group was similar to that of the M group at 1 year, 3 years, and 5 years: 94%, 76%, and 69% versus 95%, 82%, and 78% ( P = 0.3). For the combined cohorts 1 and 2, there were no significant differences in the 10‐year actuarial survival from transplant between groups. On an intention‐to‐treat basis, the dropout rate was higher in the M+ group and the 5‐year and 10‐year survival rates from listing were decreased in the M+ group. An alpha‐fetoprotein level >500 ng/mL predicted poorer outcomes for both the M and M+ groups. Conclusion : Tumor differentiation and cancer‐related symptoms of HCC can be used to select patients with advanced HCC who are appropriate candidates for liver transplantation; alpha‐fetoprotein level limitations should be incorporated in the listing criteria for patients within or beyond the Milan criteria. (Hepatology 2016;64:2077‐2088)